Public perception of common cancer misconceptions: A nationwide cross-sectional survey and analysis of over 3500 participants in Saudi Arabia - Azmi Marouf; Rama Tayeb; Ghady D. Alshehri; Hana Z. Fatani; Mohammed O. Nassif; Ali H. Farsi; Nouf Y. Akeel; Abdulaziz M. Saleem; Ali A. Samkari; Nora H. Trabulsi (Journal of Family Medicine and Primary Care, 2023)
Purpose/Background: Patients and healthcare providers use online health information and social media (SM) platforms to seek medical information. As the incidence of cancer rises, the popularity of SM platforms has yielded widespread dissemination of incorrect or misleading information about it. In this study, we aimed to assess public knowledge about incorrect cancer information and how they perceive such information in Saudi Arabia. Methods: A nationwide survey was distributed in Saudi Arabia. The survey included questions on demographics, SM platform usage, and common misleading and incorrect cancer information. Results: The sample (N = 3509, mean age 28.7 years) consisted of 70% females and 92.6% Saudi nationals. Most participants had no chronic illness. One-third were college graduates and less than one-quarter were unemployed. Conclusions: Differences in level of knowledge about cancer emerged in association with different demographic factors. Public trust in health information on SM also led to being misinformed about cancer, independent from educational level and other factors. Efforts should be made to rapidly correct this misinformation.